Developing a culturally appropriate branding for a social and emotional wellbeing intervention in an Aboriginal community - Donovan, Robert; Murray, L.; Hicks, J.; Nicholas, A.; Anwar-Mchenry, J. (Australian Health Promotion Association, 2018)
© 2018 Australian Health Promotion Association. Issue Addressed: An initial consultation process to implement a culturally appropriate social and emotional wellbeing campaign in an Aboriginal community indicated that the fundamental principles of the Act-Belong-Commit mental health promotion campaign were acceptable, but that a cultural adaptation of the branding should be sought. Methods: A competition was held inviting community members to design a brand logo for the campaign in their community. Local judges selected "winners" in various categories, and six of the submissions were selected for testing in the broader community via street intercept interviews. Respondents were asked which logo they liked best, their perceived meanings of the designs and the perceived appropriateness of the designs for a social and emotional wellbeing campaign. Results: A convenience sample of N = 26 local Aboriginal people who lived and/or worked in Roebourne completed the questionnaire. There was a clear majority preference for logo "D," which communicated appropriate meanings of pride and strength in standing together, and reflected the underlying strengths and capacities of Aboriginal people which this project seeks to harness and support. Conclusions: The approach of using a logo competition to develop the campaign brand was highly successful and enabled further meaningful engagement with the community and other service providers in the town. The success of the competition process resulted from an emphasis on relationship building, listening to the local community and involving the community in decision-making. So what? By conforming to established, but not always adhered to, recommendations for community consultation, successful and more enduring outcomes are likely.